One-loop corrections to the primordial tensor spectrum from massless isocurvature fields - Tan, Hai Siong (2020)
We study one-loop corrections to the two-point correlation function of tensor perturbations in primordial cosmology induced by massless spectator matter fields. Using the Schwinger-Keldysh formalism in cosmological perturbation theory, we employ dimensional regularization and cutoff regularization to study the finite quantum corrections at one-loop arising from isocurvature fields of the massless scalar, fermion and abelian gauge field which are freely propagating on the FRW spacetime. For all cases, we find a logarithmic running of the form Cq3H4M4p log (Hμ) where C is a negative constant related to the beta function, H is the Hubble parameter at horizon exit and μ is the renormalization scale.